Plastid phylogenomics contributes to the taxonomic revision of taxa within the genus Sanicula L. and acceptance of two new members of the genus - Song, Bo-Ni; Liu, Chang-Kun; Ren, Ting; Xiao, Yu-Lin; Chen, Lian; Xie, Deng-Feng; He, An-Guo; Xu, Ping; Fan, Xing; Zhou, Song-Dong; He, Xing-Jin (Frontiers in Plant Science, 2024)
The genus Sanicula L. is a taxonomically complicated taxa within Apiaceae, as its high variability in morphology. Although taxonomists have performed several taxonomic revisions for this genus, the interspecific relationships and species boundaries have not been satisfactorily resolved, especially for those endemic to China. This study mainly focused on S. giraldii var. ovicalycina, S. tienmuensis var. pauciflora, S. orthacantha var. stolonifera and also described two new members of the genus. We newly sequenced sixteen plastomes from nine Sanicula species. Combined with eleven plastomes previously reported by us and one plastome downloaded, we performed a comprehensively plastid phylogenomics analyses of 21 Sanicula taxa. The comparative results showed that 21 Sanicula plastomes in their structure and features were highly conserved and further justified that two new species were indeed members of Sanicula. Nevertheless, eleven mutation hotspot regions were still identified. Phylogenetic analyses based on plastome data and the ITS sequences strongly supported that these three varieties were clearly distant from three type varieties. The results implied that these three varieties should be considered as three independent species, which were further justified by their multiple morphological characters. Therefore, revising these three varieties into three independent species was reasonable and convincing. Moreover, we also identified and described two new Sanicula species (S. hanyuanensis and S. langaoensis) from Sichuan and Shanxi, China, respectively. Based on their distinct morphological characteristics and molecular phylogenetic analysis, two new species were included in Sanicula. In summary, our study impelled the revisions of Sanicula members and improved the taxonomic system of the genus.